Bibliography of N.M. Minsky’s Works. Part 1. Poetic texts - Sergei V. Sapozhkov (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2021)
This publication is the first part of the bibliography of works by the famous poet, playwright, critic, translator Nikolai Minsky (1855/1856–1937). It includes a list of the first publications of Minsky's poems (lyrics, narrative poems, poetic dramas). Both the works included in lifetime collections and those published in periodicals, as well as those remaining in manuscripts, are taken into account. When compiling the list, the author relied on the data of A.D. Alexeyev (Pushkin House), as well as personal continuous viewing of journal and newspaper periodicals, both domestic and émigré, for 1877–1937. In total, about 50 titles of journals, newspapers and almanacs of the pre-revolutionary period and about 17 titles of the same branches of periodicals of the émigré period were viewed. When describing the title of an individual poem, the compiler of the list took into account its following components: title; subtitle; revision of the first line; the presence or absence of dedication. The list reflects cases of changes in each of these components for all author collections. Reprints in non-author collections are not included. It is planned to continue the bibliography in the next issues of the journal.